Developers' strategies in dealing with planning controls : its impact on the urban housing development - Othman, Asiah (CRES, FKSG, 2006)
The private housing developers, who are now the main provider of residential units in the country, have been able to influÂence and shape the urban housing. This has been made possible through the strategies adopted in overcoming the probÂlems and constraints imposed on them, particularly in dealing with the application of planning permission. The imposition of planning controls towards housing developers in Malaysia has its implication not only in creating a good urban living environment, but at the same it has some impacts on the price due to the developers' strategies. Thus, it is the concern of this paper to look into the impacts of the developers' strategies on housing development that have some implication on the formulation of national housing policy.